PECULIARITIES IN DISTRIBUTION OF MIZELLEUS INDICUS JAIN, 1957, ON THE GILLS OF A FRESHWATER CATFISH WALLAGO ATTU (BLOCH & SCHNEIDER) - AGRAWAL, N.; MISHRA, BINDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1992)
An attempt has been made to study the peculiarities in distribution of Mizelleus indicus Jain, 1957, on the gills of a freshwater catfish, Wallago attu (Bloch & Schneider) with regard to the gill arches, sides of hemibranchs (anterior and posterior) and their sections (dorsal, medial and ventral).